Analisis Kesulitan Siswa dalam Menyelesaikan Soal Kemampuan Berfikir Logis Matematis - Anisa Kurnia Septiya Utami; Haerudin Haerudin (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to determine how the students’ difficulties in solving the test questions with indicators of the logical-mathematical thinking ability in one of the geometry materials, especially cubes. This study was conducted according to the facts in 9th-grade of SMP Negeri (State Junior High School)in one of the schools in Karawang Regency. This study used descriptive research with a qualitative approach.  The data were collected by an essay test consisting of 4 questions, and interviews. The subjects of the study were 28 9th-grade students of SMPN 1 Cikampek Karawang Regency. The instrument of the study used the essay test with indicators of logical-mathematical thinking ability according to (Andini, 2017): (1) The ability to conclude based on the appropriate portion; (2) The ability to conclude based on the examples; 3) The ability to conclude based on the existing data; (4) The ability to conclude based on the relationship between two variables. The data analysis techniques used were data collection, data reduction, data presenting, and concluding. The results of the study in the geometry materials show that all indicators of logical-mathematical thinking ability have not been achieved maximally. Only students with high category who meet the indicator, while the students who have moderate and low categories cannot meet the indicators. Out of 28 students, 3 students are in the high category with a percentage of 10.71%, 75% of students are in the moderate category, and 4 students are in the low category with a percentage of 14.29%. These results of the study show that students still have difficulty understanding and mastering the concepts to solve the test questions with the indicators of logical-mathematical thinking ability.